Change of electrochemical properties of amorphous metallic alloys by thermomagnetic modification - Pereverzeva, T.; Hertsyk, O.; Kovbuz, M.; Boichyshyn, L.; Vovk, M.-M.; Kulesha, M. (Видавництво Львівської політехніки, 2013)
It was investigated influence of modification amorphous alloys based on cobalt and ferrum by variable magnetic field and heat treatment on their corrosion behavior in aggressive environment using electrochemical methods.
Keywords: amorphous alloys; cobalt; ferrum; variable magnetic field; heat treatment; potentiometry; voltamperometry